Influence of the development of human capital and social identification of the rural laborers’ mobility in rural strategy revitalization in China - Xiang, Weili; Zhu , Kunlin; Sheng-Xian Teo, Brian; Zunirah Mohd Talib , Siti (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This paper presents an empirical analysis of the relationship between human capital and rural laborers’ willingness to return to their hometowns based on the moderating effect of identity in China. The results show that the level of human capital significantly affects the willingness of the mobile population to return to their hometowns, but this effect is reversed, i.e., the increase in the level of human capital reduces the willingness of rural laborers to return to their hometowns. The urban identity of rural laborers after flowing into cities has a significant positive moderating effect on their willingness to return to their hometowns. Improving the carrying capacity of economic development in rural areas, further strengthening infrastructure construction in rural areas to provide the material basis for rural revitalization and labor force return, and at the same time strengthening the education and training of farmers to enhance their main status is recommended.